Spontaneous tumor lysis syndrome in a patient with accelerated phase chronic myeloid leukemia treated successfully with rasburicase - Abdulrahman F. Al-Mashdali (17148316) (2022)
Rationale Tumor lysis syndrome (TLS) is an oncological emergency that occurs due to diffuse tumor cell destruction with the massive release of intracellular electrolytes. Spontaneous tumor lysis syndrome (STLS) is the development of TLS before the commencement of chemotherapy. To the best of our knowledge, there are no reported cases of STLS in the chronic or accelerated phase of chronic myeloid leukemia (CML). Patient concerns A 37-year-old woman of Arabic descent with a history of CML presented with a 3-day history of nausea and abdominal pain. She had not started any new treatment for CML within the last 3 months of presentation. Diagnosis The patient was diagnosed with hyperuricemia, hyperphosphatemia, hypocalcemia, and acute kidney injury. A peripheral blood smear confirmed the accelerated CML phase. Our patient met the criteria for clinical TLS, specifically, STLS. She was also diagnosed with autoimmune hemolytic anemia. Interventions The patient was started on intravenous normal saline (200 mL/h) and rasburicase (6 mg/d). In addition, hydroxyurea was used as a cytoreductive agent. Outcomes The creatinine level returned to normal within 48 hours of rasburicase initiation. Lessons Any patient with hematological malignancy should be monitored for TLS even before the initiation of chemotherapy. The exact mechanism of spontaneous TLS remains unknown, and further studies are needed to explain the pathophysiology of this condition. Rapid initiation of rasburicase, in addition to vigorous hydration, is effective in the treatment of acute kidney injury associated with TLS. Other Information Published in: Medicine: Case Reports and Study Protocols License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1097/md9.0000000000000244